Puerarin attenuates myocardial ischemic injury and endoplasmic reticulum stress by upregulating the Mzb1 signal pathway - Xue, Jiaojiao; Ren, Haolin; Zhang, Qi; Gu, Jing; Xu, Qian; Sun, Jiaxi; Zhang, Lu; Zhou, Ming-Sheng (Frontiers in Pharmacology, 2024)
Objective: This study investigated the role of Mzb1 in puerarin protection against heart injury and dysfunction in acute myocardial infarction (AMI) mice.Methods: C57BL/6 mice were pretreated with and without puerarin at doses of 50 mg/kg and 100 mg/kg for 14 days before the establishment of AMI model. An AMI model was induced by the ligation of the left descending anterior coronary artery, and AC16 cardiomyocytes were treated with H2O2 in vitro. Echocardiography was performed to measure cardiac function. DHE staining, NADPH oxidase assay and DCFH-DA oxidative fluorescence staining were used to determine ROS production in vivo and in vitro respectively. Bioinformatics analysis was used to predict potential upstream transcription factors of Mzb1.Results: Puerarin dose-dependently reduced myocardial infarction area and injury accompanied by the improvement of cardiac function in AMI mice. AMI mice manifested an increase in myocardial oxidative stress, endoplasmic reticulum (ER) stress, apoptosis, and mitochondrial biogenesis dysfunction, which were inhibited by pretreatment with puerarin. Puerarin also prevented Mzb1 downregulation in the heart of AMI mice or H2O2-treated AC16 cells. Consistent with the in vivo findings, puerarin inhibited H2O2-induced cardiomyocyte apoptosis, ER stress and mitochondrial dysfunction, which were attenuated by siRNA Mzb1. Furthermore, JASPAR website predicted that KLF4 may be a transcription factor for Mzb1. The expression of KLF4 was partially reversed by puerarin in the cardiomyocytes injury model, and KLF4 inhibitor (Kenpaullone) inhibited Mzb1 expression and affect its function.Conclusions: These results suggest that puerarin can protect against cardiac injury by attenuating oxidative stress and endoplasmic reticulum stress through upregulating KLF4/Mzb1 pathway, and that puerarin may expand our armamentarium for the prevention and treatment of ischemic heart diseases.